Growth response of improved native breeds of chicken to diets differed in energy and protein content - Cecep Hidayat; Sofjan Iskandar; Tike Sartika; T. Wardhani (Jurnal Ilmu Ternak dan Veteriner, 2016)
The aim of doing this experiment was to observe the growth response of improved native breeds of chicken under diets differed in energy and protein content. Three groups of improved native breeds, obtained from mating of ♂KUB to ♀KUB (Line 1), of ♂SenSi to ♀KUB (Line 2) and of ♂Gaok x ♀KUB (Line 3), were subjected to three experimental diets, differed in metabolizable energy (ME) and crude protein (CP) content. The experimental diets consisted of Diet 1 (2,800 kcal ME/ kg with 17,81% CP), Diet 2 (2,950 kcal ME/ kg with 18,61% CP) and  Diet 3 (3,100 kcal ME/ kg with 19,25% CP). The experiment was designed as factorial 3 x 3 with 7 replications of each treatment combination, consisted of 5 birds per treatment combination. The chickens were raised up to 10 weeks of age. Results of the experiment showed that Line 2 (♂SenSi mated to ♀KUB) had highest body weight at 10 weeks of age (P<0.05), lowest feed conversion ratio (FCR) and highest European Production Efficiency Factor (EPEF), compared to other two lines. The appropriate diet for Line 2 was Diet 2. It could be concluded the crossbred line that was resulted from crossing of ♂SenSi to ♀KUB (Line 2), had potential to be used as improved native chicken for the industry in Indonesia supported by appropriate diet containing 2,950 kcal ME/kg with 18.61% crude protein.